Nation in imagination : essays on nationalism, sub-nationalisms, and narration - Association for Commonwealth Language and Literature Studies. Conference 2004 : Hyderabad, India); Vijayasree, C.; Association for Commonwealth Language and Literature Studies (Hyderabad : Orient Longman, 2007)
Transcript of papers presented at the 13th Triennial Conference of the Association for Commonwealth Language and Literature Studies held in August 2004 in Hyderabad India.
Includes bibliographical references and index.
Keywords: Literature, Modern -- History and criticism -- Congresses; Nationalism in literature -- Congresses